Evaluation of Spectral Indices to Detect the Thickness of Oil Slicks in Persian Gulf Using Satellite Images - Saeed Mahmodizadeh; Hassan Yousefi; Hamed Deldar (محیط زیست و مهندسی آب, 2023)
Usually, the methods used to identify oil slicks work to identify different slick parts in terms of thickness. Since the spectrum of oil slicks is affected by seawater and the physical and chemical properties of the oil, in this study, using the spectral indices of hydrocarbons (FI, RAI, HI, RG, RR, WAF) and seawater (CHL, CDOM), different thicknesses of oil slicks are investigated and To be different. The IS (index separability) mathematical model based on classroom distance was used to evaluate the spectral indices used quantitatively. The results show that the spectral indices of hydrocarbons are more suitable for distinguishing the emulsion from seawater and other parts of the oil slick. Thus, the value of the IS parameter for the FI index in order to detect and differentiate emulsions with different evaluated segments such as seawater, shining part, code 4 and code 5 are equal to 1.542, 0.967 0.423 and 0.4236, respectively, which are compared spectral indicators of seawater have larger values. On the other hand, the spectral indices of seawater are suitable for detecting the thinner parts of the oil slick .